Berwirausaha untuk Menjadi Muzakki - Rachmad, Dedy; Avivy, Ahmad Levi Fachrul (Tazkia Islamic University College, 2025)
Training on entrepreneurship to become a muzakki aims to provide an attractive platform for entrepreneurs and prospective entrepreneurs to contribute to the development of the sunnah of the Prophet Muhammad SAW which is a guide for Muslims in the world. Imitating the practice of charity in the style of the Prophet Muhammad and his companions is a reflection of humans becoming rich. This is as explained in the word of Allah surah as-shaff verses 10 and 11. This activity aims to socialize the Tazkia institute. This activity is also carried out through training and providing material related to asking for entrepreneurship to become a muzakki.